1995
DOI: 10.1128/aac.39.9.2000
|View full text |Cite
|
Sign up to set email alerts
|

Anti-human immunodeficiency virus (HIV) activities of halogenated gomisin J derivatives, new nonnucleoside inhibitors of HIV type 1 reverse transcriptase

Abstract: Lignans are phenylpropanoid dimers distributed very widely in the plant kingdom. There are various kinds of lignan depending on the mode of dimerization of phenylpropanoid. Gomisin is a dibenzocyclooctadiene-type lignan compound and a component of Schizandra fruit extracts (30-32, 70). There are various types of gomisins, A, B, C, D, E, F, G, J, and N; some possess central nervous system depressant, analgesic, antitussive, and/or Ca antagonist activities (42, 69). As for the antiviral activities of lignans, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 65 publications
(86 reference statements)
0
42
0
Order By: Relevance
“…them have been isolated by now [3,4] in which the most abundant ingredients include schisandrin, schisantherin A, deoxyshisandrin and ␥-schisandrin. Schisandra lignans have been shown to have various biological activities, such as hepatoprotective effect [5], potent antioxidative property [6], anticarcinogenic activity through the activation of key liver enzymes [7] and strong inhibiting effect on human immunodeficiency virus (HIV) [8] reported recently. Moreover, Schisandra chinensis has also been shown to increase the physical performance and recovery rates in race horses [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…them have been isolated by now [3,4] in which the most abundant ingredients include schisandrin, schisantherin A, deoxyshisandrin and ␥-schisandrin. Schisandra lignans have been shown to have various biological activities, such as hepatoprotective effect [5], potent antioxidative property [6], anticarcinogenic activity through the activation of key liver enzymes [7] and strong inhibiting effect on human immunodeficiency virus (HIV) [8] reported recently. Moreover, Schisandra chinensis has also been shown to increase the physical performance and recovery rates in race horses [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the methylenedioxy group and the dibenzocyclooctadiene skeleton is an important structural determinant of the protective effect [22]. In the course of search for natural anti-AIDS agents, it was found that some dibenzocyclooctadiene lignans significantly inhibit the HIV replication [23,24]. Some of them have also cytostatic, antiinflammatory, antiulcer, vasorelaxant and neuroleptic activities [25].…”
Section: Introductionmentioning
confidence: 95%
“…Lignans are the major effective components in Wuweizi, which are beneficial to the protection of the livers and cardiovascular systems [2][3][4][5][6]. The halogenated lignans have inhibiting effect on human immunodeficiency virus (HIV) [7]. The content of schisandrin A is considered as the quality criterion of Wuweizi.…”
Section: Introductionmentioning
confidence: 99%